'I think it's made me a different social worker now': postgraduate social work students' experiences of undertaking independent research and applying the learning in their first year of practice. Issue 6 (18th August 2021) - Vincent, Sharon; Hamilton, Ruth
ABSTRACT: There has been an international drive to ensure social work students are research-minded. However, little is known about their experiences of undertaking independent research and even less is known about whether and how they go on to apply research skills in practice. This paper presents the findings of a qualitative study which investigated the experiences of 22 postgraduate students who were studying at a university in the North East of England. Students' written critical reflections and data from semi-structured interviews which were undertaken with four of the 22 students six to twelve months after graduation were analysed thematically. Participants experienced positive and negative emotions during their research journeys. They recounted powerful learning experiences and reported that they had been able to transfer some of their learning into practice. However, they also identified that newly qualified social workers face significant constraints to research-mindedness within the practice environment. The findings confirm the importance of providing students with experiential learning opportunities to allow them to produce as well as consume research. However, in order to fully bridge the research-practice gap there may be a need to facilitate new partnerships between higher education providers and local employers with a view to strengthening research capacity.